2021 Survey of Journalism & Mass Communication Enrollments. (March 2023) - Cummins, R. Glenn; Gotlieb, Melissa R.; McLaughlin, Bryan
In contrast to 2018, the 2021 Survey of Journalism & Mass Communication Enrollments showed a decrease in undergraduate student enrollment in journalism and mass communication programs as well as decreases in the percentage of minority undergraduate and graduate students enrolled. In addition, it showed an increase in the percentage of programs reporting decreases in their operating budgets and increases in hiring freezes for faculty and staff. These findings, which undoubtedly were impacted by the COVID-19 pandemic, reflect overall trends in student enrollment and finances at colleges and universities nationwide. However, on a more positive note, the 2021 survey also showed increases in graduate student enrollment as well as continued growth in the percentage of programs offering online degrees and the percentage of students enrolled in journalism sequences.